LANDSLIDE HAZARD MAPPING IN SIBOLANGIT DISTRICT, NORTH SUMATRA PROVINCE USING GEOGRAPHIC INFORMATION SYSTEMS - Panjaitan, Frandica; Somantri, Lili; Maruddani, Rizki Feroza; Kartikasari, Ika (Jurnal Tanah dan Sumberdaya Lahan, 2025)
The purpose of this study was to find out and describe the use of GIS in mapping the level of landslide vulnerability in Sibolangit District, Deli Serdang Regency, North Sumatra. The model used referred to the estimation of the 2004 Puslittanak, as it utilizes parameters that are easy to measure, widely available, and in accordance with the territory of Indonesia. These parameters include rainfall, rock type, soil type, slope gradient, and land cover.  The research methods used were overlay, scoring, and weighting. In the mapping process, each parameter had a score of classification multiplied by the weight of each parameter, then the results of the multiplication of the scores and weights were summed based on the suitability of their geographical location. The results of the study showed that the Sibolangit District area had the potential for landslides from low, medium to high levels. Based on the landslide disaster prediction model, the study area predominantly fell under the moderate susceptibility class, covering 15 villages. Additionally, 10 villages were identified with low vulnerability level and 5 villages with high vulnerability level. The use of GIS was also used to see the size of each area in Sibolangit District based on the level of vulnerability to landslide disasters. The level of validity of this map is quite good because it uses official data and methods suitable for the territory of Indonesia. Thus, it is accurate enough for the purpose of vulnerability identification and landslide disaster mitigation planning.